A non-contact end-effector for the handling of garments - Ozcelik, B; Erzincanli, F (Cambridge Univ Press, 2002)
In order to handle a material with either a delicate surface or an air permeable structure, a novel nozzle was designed and developed. This nozzle utilises the phenomena of the radial air outflow. It is envisaged that this new nozzle will handle materials by eliminating surface marking and air permeable structure problems.
Keywords: handling; garment; end-effector; gripper; fabric